2021
DOI: 10.1371/journal.pone.0247278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on “evaporation paradox” in province of Jiangsu in southeastern China

Abstract: Contrary to the common expectation that the reference evapotranspiration (ETo), which is an indicator of the atmospheric evaporation capability, increases in warming climate, the decline of the ETo has been reported worldwide, and this contradiction between the expected increasing ETo and the observed decreasing one is now termed the “evaporation paradox”. Based on the updated meteorological data (1960–2019), we separately detected the spatiotemporal characteristics and the causes of the “evaporation paradox” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…The Evaporation paradox is the reported decreasing trends in PE (or RET) until the mid-1980s (or mid-1990s for regions in USA and Australia; Table 1) which contradicted the anticipated long-term increasing trends in the atmospheric evaporative demand, in a concurrently warming atmosphere [54,55]. The latter phenomenon is important since PE is considered "a clue to the direction of the change in AET" [56].…”
Section: The Conflict Of Increasing and Decreasing Trends Of Et Typesmentioning
confidence: 99%
“…The Evaporation paradox is the reported decreasing trends in PE (or RET) until the mid-1980s (or mid-1990s for regions in USA and Australia; Table 1) which contradicted the anticipated long-term increasing trends in the atmospheric evaporative demand, in a concurrently warming atmosphere [54,55]. The latter phenomenon is important since PE is considered "a clue to the direction of the change in AET" [56].…”
Section: The Conflict Of Increasing and Decreasing Trends Of Et Typesmentioning
confidence: 99%
“…We also analyzed the effects of SSH and WS, which were included in only a few previous studies, and found that both contributed positively to the HI trend in Jiangsu province (Figure 5). Our previous study found that, for Jiangsu province in 1960-2019, the decrease in RH and SSH decreased ET o [69], which increased HI.…”
Section: Contributions Of Meteorological Variables To Humidity Index ...mentioning
confidence: 90%
“…Indeed, while the projections in AED are expected to follow the predicted increase in temperature, AET is more correlated to the decreasing rainfall. Moreover, evidence of the so-called “evaporation paradox” (Dimitriadou and Nikolakopoulos 2021 ; Qin et al 2021 ) has been reported worldwide, with observed pan evaporation or RET that have decreased along with the continuous increase in temperature over the past decades. All this suggests the use of more integrated approaches to better quantify the surface-atmosphere interactions under climate change (Milly and Dunne 2016 ; Tramblay et al 2018 ).…”
Section: Challenges and Uncertainties In Climate Change Modeling And ...mentioning
confidence: 99%